Rare Association of Congenital Facial Palsy, Bilateral Microtia and Congenital Heart Disease - Rawat, Aditi; Bhil, Dipika; Javadekar, Bakul B (Journal of Nepal Paediatric Society, 2018)
We report a case of a two day old female child with congenital facial palsy, bilateral microtia, congenital heart disease, renal ectopia and unilateral hypoplasia of depressor anguli oris muscle. These constellation of symptoms have not been found together in any case before. This unknown syndrome could be considered to be in a gray zone between Caylers Cardiofacial syndrome and Pearls syndrome.